Nanovesicles of cholesterol-free enable malignant tumor-specific magnetic resonance imaging - Zhilin Zhang; Guochao Nie; Yunting Deng; Lonli Song; Wangqiang Wei; Huali Li; Mengfei Lu; Dongxian Qin; Yulin Yan (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2021)
There are many patents for magnetic nanoparticles as tumor magnetic resonance imaging enhancers, but the gadolinium complexes commonly used in the clinic are difficult to target the diseased tissues, while nanoliposomes are ideal carriers for anti-tumor drugs. Owing to that the commonly used liposome particle size is too large, poor stability, the Cholesterol was used to increase the stability of nanoparticles or reduce their diameter. This foreign cholesterol may also have toxic side effects on patients. And the existing liquid film process cannot be large-scale production. The aim of this paper is to overcome the shortcomings of the prior art, then put forward a new method for preparing cholesterol-free tumor magnetic resonance imaging enhancer based on nano liposome encapsulation was proposed. We can obtain tumor magnetic resonance imaging enhancers with low toxicity and a good ability to cross biofilm. Finally, the facile fabrication was proved according to applications.